Food and lifestyle education in Tuscan schoolchildren: 2018-2019 follow-up of a long-term campaign. (20th October 2021) - Tarroni, M; Messina, D; Balestri, C; Cocchi, F; Messina, G; Nante, N
Abstract: Background: Nutritional profile, physical activity level and sedentary behaviours, in preteen age, are determinants able to influence both short and long-term state of health, therefore succeeding in health education campaigns addressed to this age group is critical for the interested population. Is currently underway the multiannual follow-up of the Italian "sCOOL FOOD - Per un Futuro di tutto Rispetto" project of Monte dei Paschi Foundation of Siena, Tuscany, which offers year-round cycles of classes and workshops about the themes listed above. Our objective was to assess whether this intervention could significantly influence over time healthy, and unhealthy, behaviours of the participants. Methods: We structured the follow-up as a prospective cohort study with one-group pretest-posttest design. We used the CAWI technique, building a questionnaire based on the Italian "OKkio alla Salute" survey, and collected data from the whole population of students enrolled in the project (in the school year 2018-2019 they were 3787, aged from 7 to 12) before and after the intervention. Afterwards, we conducted paired data analysis on the frequencies of specific behaviours. Results: We analysed paired data from 310 respondents. Improvements were gained in: afternoon TV watching (OR 0.54; 0.34 - 0.84; p < 0.01), consumption of sweet (OR 0.39; 0.16 - 0.88; p < 0.05) and salty (0.42; 0.18 - 0.90; p < 0.05) snacks, attitude to play outdoors after school (OR 2.6; 1.21 - 6.04; p < 0.01), sedentary behaviour in leisure time (OR 0.27; 0.16 - 0.44; p < 0.0001), mean weekly sport activity (+0.14 days; +0.02 - +0.27; p < 0.05). No variable has deteriorated. Conclusions: The improved compliance with healthy behaviours in the participants at this project suggests its viability as a health promotion campaign. Further parallel surveys on control groups are pending, in order to control potential confounders such as the seasonality of some habits and the awareness of the participants on the addressed subjects. Key messages: A coordinated and cross-disciplinary food and lifestyle year-round education campaign at school can affect health determinants of children. School can correct unfavourable eating and lifestyle behaviours determined by family habits.